HUBUNGAN PENGETAHUAN IBU DENGAN PERILAKU PENCEGAHAN STUNTING PADA ANAK: Pengetahuan Ibu, Stunting, Perilaku - Putra, Mega Revangga; Yulianto, Yoyok (WELL BEING, 2025)
Stunting in toddlers, caused by chronic malnutrition, negatively affects their growth and development. Mothers play a crucial role in preventing stunting, as they are the primary caregivers from pregnancy through early childhood. This study aimed to describe mothers' knowledge and behavior in stunting prevention at Posyandu Jasmine Blabak, Kediri Regency. A descriptive, cross-sectional design was used with 40 randomly selected mothers as respondents. Data were collected through self-administered questionnaires and analyzed using univariate methods. The results showed that 67.5% of mothers had good knowledge about stunting, while 75% demonstrated fairly good preventive behavior. In conclusion, most mothers had sufficient knowledge and behavior regarding stunting prevention.